SCIENTIFIC HERITAGE OF PROFESSOR O. V. SMIRNOVA IN FOREST ECOLOGY (TO THE 85TH ANNIVERSARY) - O. I. Evstigneev (Вопросы лесной науки)
O. V. Smirnova is a professor, doctor of biological sciences, and a leading scientist in the field of plant demography, population biology, and forest biogeocenology. O. V.Smirnova’s biogeocenotic views are based on ideas about the population organization of living cover, which were formed under the influence of her teacher, prof. A. A. Uranov. Within the framework of this system of views, O. V. Smirnova made a significant contribution to the development of concepts of the biological age of plants and the population strategy of plants, to the creation of the theory of coenopopulations and the population organization of biogeocenoses, as well as to the formation of ideas about modern zonality as an anthropogenic phenomenon. The article provides a complete bibliography of O. V. Smirnova’s papers, including the titles of her PhD students’ dissertations.